Studying Multiple Aspects and Impacts of Chatbots: A Systematic Mapping Study - Mohammed , Alfarooq; Abdalla, Abdalmunam (AlQalam Journal of Medical and Applied Sciences, 2026)
The usage and deployment of chatbots are increasing in many sectors, such as education and healthcare systems. Those interactive systems are designed to provide automated responses to users 24 hours a day, and are capable of collecting data from users and helping in making decisions. With the stunning emergence of some chatbots recently, for instance, ChatGPT, many researchers have started studying chatbots from different perspectives. Some studies, for example, focus on the usage and deployments, while others investigate evaluation and classification. Despite the fame and great momentum that chatbots are having now, there are still many aspects that have not been studied well. For example, there is a lack of information about its correctness, impact, and best usage in some areas. In this paper, we remove the ambiguity and discover other impacts and characteristics of chatbots in different areas. To answer our research questions, we conducted a systematic mapping study using a search strategy on a well-known database, and then we discussed our mapping results. We identified a final number of 128 papers published between 2018 and September 2023. We observed some trends related to chatbots, like problems with correctness and reliability, besides successful usage and implementation in some areas and sectors. We also discovered some positive and negative influences of chatbots on humans. We believe that our results presented in this paper will be very useful and important where chatbots are being used, whether in the industry or in the scientific field. Overall, more efforts and research need to be conducted on chatbots.